Technological Engineering for Traditional Coconut Oil Making - Ni Made Defy Janurianti; I Wayan Sudiarta; Anak Agung Made Semariyani (SEAS (Sustainable Environment Agricultural Science), 2018)
This study aims to determine the effect of pineapple extract concentration and duration of fermentation on the characteristics and good quantity and to determine the concentration of pineapple extract and fermentation duration that can produce coconut oil with the highest yield with characteristics that meet Indonesian National Standard No. 01-2902-1999. This research was carried out at the Food Analysis Laboratory, Faculty of Agriculture, Universitas Warmadewa. This research is a factorial experiment with Randomized Block Design (RBD) consisting of 2 (two) factors, namely: factor I, pineapple extract concentration composed of 4 levels, namely pineapple extract concentration 10%, 15%, 20%, and 25%. Factor II, fermentation duration consisting of 3 degrees, 12 hours, 24 hours and 36 hours. The variables observed for coconut oil include objective observations namely analysis of oil yield, water content, free fatty acid levels, peroxide numbers, levels of impurities and acid numbers. While subjective views include the test of flavor, color, taste and overall acceptance, the best quality of coconut oil is objectively obtained in the addition of 15% pineapple extract with 12 hours of fermentation. Subjectively the influence of each treatment on the highest variable of color, flavor, taste, and acceptance was obtained in the addition of 25% pineapple extract with 12 hours of fermentation. Compared to Indonesian National Standard No. 01-2902-1999 found that the tested variables met the requirements except for oil impurities that were still very high (more than 0.05%) and the water content in the pineapple extract treatment was 10%, and fermentation duration was 36 hours exceeding the standard of 0.533% (SNI requirements maximum of 0.5%).